Advanced Analytical Methods in Tribology (Microtechnology and MEMS,, 2018)
Friction and wear phenomena are governed by processes at the interface of sliding surfaces. For a detailed understanding of these phenomena many surface sensitive techniques have become available in recent years. This book gives an overview of the basics and methods of state-of-the-art nanoscale analytical techniques for researchers and practitioners in the field of tribology. It provides guidance and shows examples of the application of mechanical, microstructural, chemical characterization methods and topography analysis of materials. The applied methods are atom probe tomography, TEM, SERS, NEXAFS, in-situ XPS, nanoindentation and in situ Raman spectroscopy. A survey of related numerical calculations completes the book. These include ab-initio and molecular dynamics coupling, numerical calculations for mechanical aspects and density functional theory to study chemical reactivity.